Harry's trees eaudiobook - Cohen, Jon (2018)
A grieving widower, a determined girl, a courageous librarian and a mysterious book come together in an uplifting tale of love, loss, friendship and redemption. Thirty-four-year-old Harry Crane works as an analyst for the US Forest Service. When his wife dies suddenly, Harry, despairing, retreats north to lose himself in the remote woods of the Endless Mountains of Pennsylvania. But fate intervenes in the form of a fiercely determined young girl named Oriana. She and her mother, Amanda, are struggling to pick up the pieces from their own tragic loss of Oriana's father. Discovering Harry while roaming the forest, Oriana believes that he holds the key to righting her world. Harry reluctantly agrees to help Oriana carry out an astonishing scheme inspired by a book given to her by the town librarian, Olive Perkins. Together, Harry and Oriana embark on a golden adventure that will fulfill Oriana's wild dream—and ultimately open Harry's heart to new life.